Surface Nonlinear Gratings by Direct Multiphoton Microscope Writing. Issue 4 (1st December 2017) - Avalos‐Hernández, Jonathan; Carriles, Ramon; Domínguez‐Juárez, Jorge Luis
Abstract : Thin film fabrication and patterning using organic molecules is of interest for technological and optoelectronic applications, among others. We demonstrate a new method to realize surface periodic patterning using femtosecond laser radiation from a multiphoton microscope. The laser is focused on organic films to generate a homogeneous 2D structure on a flat surface. The organic film was deposited onto microscope slides by immersion. From the gratings, the relative position of the nonlinearly diffracted first order maxima of second harmonic generation was measured. It is shown that nonlinear diffraction orders can be manipulated by the characteristics of the surface periodic patterning. It is possible to extend this writing scheme to arbitrary patterns and possibly curved surfaces with potential applications in couplers and waveguides. This method might also be useful to perform selective linear and nonlinear spectroscopy by modulating the linear and nonlinear activity of dyes deposited on the surface of microresonators or similar devices. Abstract : Avalos‐Hernández et al. write patterns on organic thin films deposited on glass using an ultrafast laser coupled to a scanning microscope. The authors demonstrate that exposition to the laser quenches the second‐order nonlinear optical response. This technique could find applications in waveguides, couplers, plasmonics, or optoelectronics. It is possible to extend the writing scheme to arbitrary patterns and possibly curved surfaces.